Functional connectivity across multi-frequency bands in patients with tension-type headache: a resting-state fMRI retrospective study - Jili Wang; Hongjie Shen; Qinyan Xu; Shuxian Zhang; Tian Li; Yun Zheng (BMC Medical Imaging)
Abstract Objectives Tension-type headache (TTH) is the most common nervous system disorder worldwide. This study aimed to examine abnormal network-level brain functional connectivity (FC) alterations in patients with TTH across multi-frequency bands. Methods The study enrolled 63 subjects, comprising 32 patients with TTH and 31 healthy controls (HC). According to our team's previous research, the brain regions with abnormal ReHo in the conventional frequency band (0.01–0.08 Hz) and the slow-5 band (0.01–0.027 Hz) were chosen as seed regions of interest (ROIs). Subsequently, the FC between ROIs and the entire brain analysis across various frequency bands was calculated to evaluate network-level alterations, and differences between the TTH and HC were analyzed. Pearson’s correlation analysis was conducted to assess the relationship between significantly altered FC values in two frequency bands and visual analog score (VAS) in TTH patients. Results In the slow-5 band (0.01–0.027 Hz), FC between right medial superior frontal gyrus and right medial temporal pole/right inferior temporal gyrus as well as right middle frontal gyrus and left supramarginal gyrus of TTH patients exhibited significantly higher, compared to the HC group, while FC between right middle frontal gyrus and right lateral occipital cortex reduced. For the correlation results, there was no correlation between abnormal brain regions of FC and VAS score. Conclusions Changes in FC within brain regions associated with TTH are linked to pain processing. And the altered FC in TTH patients were frequency dependent. These initial observations could enhance our understanding of TTH’s pathophysiological mechanism and offer insights for its future diagnosis and treatment.